2017
DOI: 10.3892/mmr.2017.6392
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of arterial stiffness, wave reflection and air pollution

Abstract: Arterial stiffening is associated with increased cardiovascular risk. Whether exposure to relatively high levels of air pollution is associated with arterial stiffening is unclear. We aimed to assess the association between exposure to major air pollutants and arterial stiffening. PubMed, SCOPUS and Web of Science databases (through 31 January 2017) were searched using a combination of terms related to exposure to gaseous [nitrogen dioxide (NO2), nitrogen oxides (NOx) and sulphur dioxide (SO2)] or particulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
2
23
0
1
Order By: Relevance
“…No previous studies have attempted to relate air pollution to carotid artery intima-media thickness at such a young age. In adults though, there is evidence of structural arterial wall changes due to air pollution exposure [11, 56].…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies have attempted to relate air pollution to carotid artery intima-media thickness at such a young age. In adults though, there is evidence of structural arterial wall changes due to air pollution exposure [11, 56].…”
Section: Discussionmentioning
confidence: 99%
“…distance of residential address from a major road) is also linked to increased arterial stiffness, [44][45][46] although not all studies have found significant associations. 47,48 A number of studies have made use of the non-invasive techniques to measure heart rate variability (HRV). 11,49 There is an overall trend towards reduction in HRV parameters.…”
Section: Particulate Matter and Cardiovascular Diseasementioning
confidence: 99%
“…Previous studies on the association between PM 10 and baPWV showed inconsistent results due to differences in study populations and small sample sizes. In a systematic review, based on the published literature until January 2017, Zanoli et al [ 14 ] suggested that short- and long-term exposure to gaseous and PM pollutants, including nitric oxide, sulfur dioxide, PM 10 , and PM 2.5 , may be associated with increased arterial stiffness and wave reflection. As a potential marker of arterial stiffness, parameters such as carotid-femoral PWV, baPWV, and augmentation index were assessed in 11 published studies from 2010 to 2016.…”
Section: Discussionmentioning
confidence: 99%